Representation of Religious-Multicultural Values in the Design of the Pancasila Mosque - Munasib; Taufiq, Muhammad; Sumantri, Rifki Ahda; Ulul Huda; Proverawati, Atikah (Universitas Islam Malang, 2024)
This research aims to analyze the semiotic design of the Pancasila mosque in the Banyumas Regency. The approach used in this research is a multidisciplinary qualitative-interpretative approach, namely by integrating the Islamic religious science approach with semiology. The method used in this study is a semiotic method which focuses on analyzing the relationship between symbolic meanings in religious-multicultural symbols in the design of the Pancasila mosque. This research succeeded in finding religious-multicultural values ​​that are reflected in the design of the triple roof and pentagonal ornaments found in the interior and exterior design of the Pancasila mosque.